2021
DOI: 10.52142/omujecm.38.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Does recurrent pregnancy loss have an inflammatory background?

Abstract: Although several pathophysiological mechanisms are defined in etiology recurrent pregnancy loss, still causes of half of the cases haven’t revealed yet. It is reported that inflammatory processes take place in the etiology of the disease. In our study, we aimed to reveal the relationship between recurrent pregnancy loss with white blood cell count (WBC), C-reactive protein (CRP) and ferritin levels. We included our study 90 pregnant women having recurrent miscarriage history and 101 pregnant women without recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…The current study found statically significant increased abortion among women with RPL compared to control (P<0.001), this goes in run with Güvey et al (10) study which was conducted to investigate the role of ferritin, CRP and WBCs as inflammatory markers for detection of RPL and found statistically significant increased abortion among women with RPL (P-value=0.004).…”
Section: Discussionsupporting
confidence: 85%
“…The current study found statically significant increased abortion among women with RPL compared to control (P<0.001), this goes in run with Güvey et al (10) study which was conducted to investigate the role of ferritin, CRP and WBCs as inflammatory markers for detection of RPL and found statistically significant increased abortion among women with RPL (P-value=0.004).…”
Section: Discussionsupporting
confidence: 85%